CUSTOMER FOLLOW UP AND EDUCATION STRATEGY IN THE BYOND BSI DIGITAL APPLICATION MIGRATION PROCESS: A CASE STUDY AT BANK SYARIAH INDONESIA KC ASTANA ANYAR - Ade Jamarudin; Ridwan Effendi; M. Rivaldo Putra (UIN Sunan Gunung Djati Bandung, 2025)
Improving service quality, operational effectiveness, and competitiveness of financial institutions including in the context of Islamic banking is a strategic goal of digital transformation in the banking industry. Migrating Bank Syariah Indonesia (BSI) service applications from BSI Mobile to BYOND BSI is one form of real implementation of this transformation. This study examines the education and follow-up strategies applied to customers during the digital application migration process, focusing on a case study at BSI Astana Anyar Branch Office, Bandung. The method used is a descriptive qualitative approach through field observation. The results of the study indicate that an intensive communication strategy via WhatsApp messages and telephone, accompanied by technical guidance on the installation and activation of the BYOND BSI application, plays an important role in increasing customer understanding, convenience, and involvement. In addition, the availability of informative and responsive services helps build customer trust in the new digital service system. These findings conclude that the Islamic banking sector, which is adapting to advances in financial technology, can successfully adopt digital transformation if supported by a systematic follow-up strategy and a relevant educational approach.